INTEGRATING BLENDED LEARNING INTO A GENRE-BASED APPROACH TO TEACHING ACADEMIC WRITING - Sufiyandi, Sufiyandi; Emilia, Emi; Damayanti, Ika Lestari; Mukminin, Amirul (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The Genre-Based Approach (GBA) has been widely reported as an effective framework for teaching writing; however, its implementation through the teaching cycle in blended learning environments remains underexplored. This study aims to investigate how the genre-based teaching cycle is implemented in teaching writing through blended learning and how it contributes to students’ academic writing development. A qualitative case study was conducted involving 30 students enrolled in a genre writing course at the English Language Department of a university in Indonesia. Data were collected through classroom observations, students’ reflective journals, and analyses of students’ written texts by comparing the diagnostic text to those written at the independent construction stage. The study revealed that teaching academic writing through GBA in a blended learning setting led to observable improvements in the teaching-learning process through GBA stages and in students’ academic writing in terms of genre, register, discourse, grammar, and graphic features. These findings show the value of integrating face-to-face and online learning within the genre-based teaching cycle to support academic writing development. The study also provides empirical insights into how GBA can be integrated into blended learning and offers useful guidance for academic writing instruction in higher education through technology-mediated pedagogy, with broader applicability as an instructional model for science-related study programs that require structured and discipline-specific academic texts.